2000
DOI: 10.1021/jm0000113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Thiopyran Analogues of the Dopamine D3 Receptor-Selective Agonist (4aR,10bR)-(+)-trans-3,4,4a,10b- Tetrahydro-4-n-propyl-2H,5H-[1]benzopyrano[4,3-b]-1,4-oxazin-9-ol (PD 128907)

Abstract: Benzopyranoxazine (+)-7 (PD 128907) is the most dopamine (DA) D3 receptor-selective agonist presently known. The only structural feature which distinguishes 7 from the analogous nonselective naphthoxazines is an oxygen atom in the 6-position. To extend this series of tricyclic DA agonists we used a classic bioisoster approach and synthesized thiopyran analogues of 7, which have a sulfur atom in the 6-position. We prepared trans-4-n-propyl-3,4,4a,10b-tetrahydro-2H,5H-[1]benzothiopyrano[4, 3-b]-1,4-oxazin-9-ol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(61 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…We find, however, that our current striatal clozapine D2 occupancy (80 ± 7%) is very similar to that of our earlier report (80 ± 8%) in which a twofold lower injected [ 3 H]-( + )-PHNO dose was used (McCormick et al, 2008). [ 3 H]-( + )-PHNO has been reported to have 30-to 45-fold higher in vitro affinity for the D3 receptor than the D2 receptor (Freedman et al, 1994;van Vliet et al, 2000) suggesting that a lower injected dose may be required to fulfill tracer dose conditions for D3 compared with D2. In the absence of reports comparing the in vivo affinity of [ 3 H]-( + )-PHNO, it remains possible that the tracer dose range has been exceeded with respect to the D3 receptor, consequently presenting the possibility of underestimated drug D3 receptor occupancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find, however, that our current striatal clozapine D2 occupancy (80 ± 7%) is very similar to that of our earlier report (80 ± 8%) in which a twofold lower injected [ 3 H]-( + )-PHNO dose was used (McCormick et al, 2008). [ 3 H]-( + )-PHNO has been reported to have 30-to 45-fold higher in vitro affinity for the D3 receptor than the D2 receptor (Freedman et al, 1994;van Vliet et al, 2000) suggesting that a lower injected dose may be required to fulfill tracer dose conditions for D3 compared with D2. In the absence of reports comparing the in vivo affinity of [ 3 H]-( + )-PHNO, it remains possible that the tracer dose range has been exceeded with respect to the D3 receptor, consequently presenting the possibility of underestimated drug D3 receptor occupancy.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with its high in vitro affinity for both D2 and D3 receptors (Freedman et al, 1994;van Vliet et al, 2000), the agonist positron emission tomography (PET) radiotracer [ 11 C]-( + )-PHNO is thought to label both receptor subtypes in vivo. In both human and baboon, the regional pattern of in vivo [ 11 C]-( + )-PHNO binding is unique among D2/D3 radiotracers, with highest binding in the globus pallidus (GP) followed by ventral striatum (VS), caudate (CAU) and putamen (PUT), and substantia nigra (SN) (Ginovart et al, 2007;Narendran et al, 2006;Willeit et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…24,26 Sumanirole also has a 250-fold selectivity for D2 over D3 receptors, 26 but the affinity of PD-128907 for D 3 R is only 15 to 30 times higher than that for D2R in rats. 23 Thus, sumanirole is unlikely to interact efficiently with D3R at relevant pharmacological concentrations, but PD-128907, depending on the dose used, may act as a D3R or a D2/D3R agonist. 25,26,30 Pharmacological and genetic studies have provided strong evidence that two very characteristic effects of DA agonists, hypothermia and yawning, are mediated by D2R and D3R respectively.…”
Section: Discussionmentioning
confidence: 99%
“…19, 20, 21 In the present study, we therefore set out to determine the respective contributions of these DA receptors in the reversal of the motivational and affective impairments induced by SNc DA neuronal loss. Using DA agonists selective for D 1 R (SKF-38393), D 2 R (sumanirole) or preferential for D3R (PD-128907), 22, 23, 24, 25, 26 we showed that all DA agonists corrected the affective impairments, but only the preferential D3R agonist reversed the motivational deficits induced by the SNc DA lesions, providing a potential specific target for the treatment of PD-related neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 96%
“…Bioisosterism is a concept that continues to be widely applied in medicinal chemistry to make informed modifications to potential new drug compounds [1][2][3][4][5][6][7][8]. These modifications make it possible to alter key properties such as solubility or toxicity while the activity of a molecule is enhanced or maintained.…”
Section: Introductionmentioning
confidence: 99%